2019
DOI: 10.1038/s41467-019-09929-w
|View full text |Cite
|
Sign up to set email alerts
|

The K219T-Lamin mutation induces conduction defects through epigenetic inhibition of SCN5A in human cardiac laminopathy

Abstract: Mutations in LMNA , which encodes the nuclear proteins Lamin A/C, can cause cardiomyopathy and conduction disorders. Here, we employ induced pluripotent stem cells (iPSCs) generated from human cells carrying heterozygous K219T mutation on LMNA to develop a disease model. Cardiomyocytes differentiated from these iPSCs, and which thus carry K219T- LMNA , have altered action potential, reduced peak sodium current and diminished conduction veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 71 publications
(90 reference statements)
5
63
0
Order By: Relevance
“…The ensemble of lamins, chromatin marks and PcG factors around LADs creates a repressive environment 14,15 , with heterochromatin and PcG target regions adjacent to each other 16,17 . In line with these observations, we previously demonstrated that Lamin A functionally interacts with PcG 18,19 , as later also reported by others 17,[20][21][22] .…”
supporting
confidence: 90%
“…The ensemble of lamins, chromatin marks and PcG factors around LADs creates a repressive environment 14,15 , with heterochromatin and PcG target regions adjacent to each other 16,17 . In line with these observations, we previously demonstrated that Lamin A functionally interacts with PcG 18,19 , as later also reported by others 17,[20][21][22] .…”
supporting
confidence: 90%
“…In addition, thanks to its interaction with the LINC complex, desmin acts as a hub in transducing stimuli deriving from the ECM into the nucleus. Mutations in desmin, lamin or nesprins are associated with severe cardiac disease . Mice heterozygous for a lamin A mutation show decreased response to left‐ventricular pressure overload, due to impaired activation of the mechanosensitive gene Egr‐1 .…”
Section: Intermediate Filaments and Propagation Of Mechanosensing To mentioning
confidence: 99%
“…However, this phenotypic readout appears to be more variable in hiPSC-CMs; although Bertero et al (6) and Lee et al (5) differentiated hiPSCs into CMs using the same protocol (14), only Lee et al detected abnormal nuclear structures. Notably, Salvarani et al (11) also did not detect nuclear shape defects in LMNA mutant CMs (albeit using a different protocol), in contrast with previous observations on primary cells and mature adult CMs from affected patients with the same K219T mutation. Even though these discrepancies could be ascribed to the different LMNA genotypes of the bi-dimensional hiPSC-CM cultures of the three studies, it is likely that a platform mimicking the three-dimensional tissue architecture and stresses to which CMs are subjected in vivo might be required to consistently unravel nuclear shape abnormalities in cardiac muscle, as was the case for skeletal muscle (13, 15).…”
mentioning
confidence: 63%
“…One appealing possibility is that lamin A/C might exert this function cooperating with other epigenetic modifiers. Interestingly, lamin A/C mediates Polycomb repressive complex 2 (PRC2) recruitment to specific loci (10), and K219T-LMNA has recently been shown to induce aberrant PRC2 targeting and silencing of genes associated with the conduction defects of cardiac laminopathy in hiPSC-CMs (11). LMNA mutations might dysregulate transcriptional programs via defective Polycomb recruitment and epigenetic silencing.…”
mentioning
confidence: 99%